Assessment of Bacteriological Quality of Fast Foods and Soft Drinks in Relation to Safety and Hygiene (Bangladesh Journal of Microbiology, 2010)
Bacteriological quality assessment of fast foods and soft drinks of different establishments of Dhaka City was carried out. For systematic study of varieties of such foods consumed by different class of people, the food samples were divided into four major categories: Type A (upper class), Type B (middle class), Type C (moderate class) and Type D (lower class). The quality of samples was assessed by determining standard plate count (SPC). The SPC showed that about 15% of Type A, 23% of Type B, 43% of Type C and 57% of Type D samples were unsafe for human consumption. Coliform bacteria were detected in about 13-48% of various food varieties. Psychrophilic bacteria were present in about 19-42% samples, indicating not suitable for longterm preservation in refrigeration condition. One sample of Type A and two samples each of Type B, Type C and Type D yielded growth of Salmonella and a considerable number of the samples contained Escherichia coli. In this study it was found that the condition of most of the Type C and Type D food and drinks were unsafe for consumption. The safely and hygienic status of Type A and Type B were comparatively better than those of Type C and Type D. Keywords: Bacteriological quality; Fast food; Soft drink; Safety; HygieneDOI: http://dx.doi.org/10.3329/bjm.v25i1.4863 Bangladesh J Microbiol, Volume 25, Number 1, June 2008, pp 73-75